Is MRI Overutilized for Evaluation of Knee Pain in Veterans? - Koenig, Scott; Morcos, George; Gopinath, Rohan; Wang, Kenneth; Henn, Frank, 3rd; Leong, Natalie L. (The Journal of Knee Surgery, 2021)
MRI is an essential diagnostic imaging modality for many knee conditions; however, it is not indicated in the setting of advanced knee arthritis. Inappropriate MRI imaging adds to health care costs and may delay definitive management for many patients. The primary purpose of this study was to ascertain the frequency of inappropriate MRI scans performed at one Veterans' Administration Medical Center (VAMC). We performed a retrospective chart review of all knee MRIs ordered over a 6-month period. Inappropriate MRI was defined as MRI performed prior to radiographs (XRs), or in the presence of XRs demonstrating severe osteoarthritis, without leading to a nonarthroplasty procedure of the knee. Of the 304 cases reviewed, 36.8% (112) of the MRIs were deemed inappropriate, 33 were ordered by orthopedists, and 79 were ordered by other health care providers. Of the 33 ordered by orthopedists, 25 were ordered by retired/nonsurgical orthopedists. Obtaining an MRI delayed care by an average of 29.2 days. Of the 252 cases that had XR prior to MRI, none included all four views in the standard knee XR series and only four had weightbearing images. Over a third of knee MRIs performed at this VAMC were inappropriate and delayed care. Additionally, no XRs in our study contained all the necessary views to properly assess knee arthritis. These concerning findings signify a potential opportunity for education in diagnostic strategies, to better patient care and resource utilization in the VAMC.
Keywords: MRI; osteoarthritis; knee pain; veterans